2012
DOI: 10.1590/s1516-89132012000500003
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi occurring in Ipomoea carnea tissues and their antimicrobial potentials

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Approximately 300,000 plant species growing in unexplored area on the earth are host to one or more endophytes. 3 , 4 One of these plants is Zingiber spectabile (common name Beehive Ginger), a member of the ginger family, which is used as an ethnobotanical plant in many countries, especially in South-East Asia. Ginger is used as a remedy ingredient to treat a wide range of diseases including cancer 5 and arthritis, 6 , 7 and it is also used as an antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 300,000 plant species growing in unexplored area on the earth are host to one or more endophytes. 3 , 4 One of these plants is Zingiber spectabile (common name Beehive Ginger), a member of the ginger family, which is used as an ethnobotanical plant in many countries, especially in South-East Asia. Ginger is used as a remedy ingredient to treat a wide range of diseases including cancer 5 and arthritis, 6 , 7 and it is also used as an antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies can be found in the literature using an isolation temperature of 18°C (Souza et al, 2004). In general, temperatures between 25 and 30°C are commonly used (Lima et al, 2011;Banhos et al, 2014;Bongiorno et al, 2016) or an ambient temperature of 28°C (Costa et al, 2012;Tayung et al, 2012), showing a large variation in this environmental factor (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Poisoned food technique has been used in many such studies in order to evaluate the antifungal potential of the crude extracts against fungal pathogens [65,66]. The literature reviewed also indicated that ethyl acetate solvent was commonly used in the extraction of antimicrobial compounds [67,68]. The percentage inhibition in the radial growth of pathogen caused by different isolates of C. longa was also recorded (Table 3).…”
Section: Evaluation Of Endophytic Fungal Isolates and Crude Fungal Exmentioning
confidence: 99%